Cancer cell-derived immunoglobulin G activates platelets by binding to platelet FcγRIIa - Miao, Shuo; Shu, Dan; Zhu, Ying; Lu, Meng; Zhang, Qingsong; Pei, Youliang; He, Ao-Di; Ma, Rong; Zhang, Bixiang; Ming, Zhang-Yin (Cell death & disease, 2019)
Tumor-associated thrombosis is the second leading risk factor for cancer patient death, and platelets activity is abnormal in cancer patients. Discovering the mechanism of platelet activation and providing effective targets for therapy are urgently needed. Cancer cell- derived IgG has been reported to regulate development of tumors. However, studies on the functions of cancer cell-derived IgG are quite limited. Here we investigated the potential role of cancer cell-derived IgG in platelet activation. We detected the expression of CD62P on platelets by flow cytometry and analyzed platelet function by platelets aggregation and ATP release. The content of IgG in cancer cell supernatants was detected by enzyme-linked immune sorbent assay. The distribution of cancer-derived IgG in cancer cells was analyzed by immunofluorescence assay. Western blot was performed to quantify the relative expression of FcγRIIa, syk, PLCγ2. The interaction between cancer cell-derived IgG and platelet FcγRIIa was analyzed by co-immunoprecipitation. The results showed that higher levels of CD62P were observed in cancer patients’ platelets compared with that of healthy volunteers. Cancer cell culture supernatants increased platelet CD62P and PAC-1 expression, sensitive platelet aggregation and ATP release in response to agonists, while blocking FcγRIIa or knocking down IgG reduced the activation of platelets. Coimmunoprecipitation results showed that cancer cell-derived IgG interacted directly with platelet FcγRIIa. In addition, platelet FcγRIIa was highly expressed in liver cancer patients. In summary, cancer cell-derived IgG interacted directly with FcγRIIa and activated platelets; targeting this interaction may be an approach to prevent and treat tumor-associated thrombosis.